Religion, Gender, and the Development of Leisure Time Activities from Adolescence to Young Adulthood: The Case of Muslim Girls in Germany - David Kretschmer; Lars Leszczensky (Socius, 2025)
Previous research shows that Muslim girls in Western societies are less likely to do sports than both Muslim boys and non-Muslims of either gender. But we know little about whether other leisure time activities also differ by religion and gender and whether these patterns change during the transition from adolescence to young adulthood. In this data visualization, we use large-scale representative data from Germany to show how 13 leisure time activities of Muslim and non-Muslim boys and girls develop from adolescence to young adulthood. Muslim girls are more involved in housework than other youth but are least active in doing sports and other activities that involve mingling beyond the immediate peer group, such as going out or attending clubs. There are few differences in other activities, such as reading, watching TV, or visiting relatives. Moreover, Muslim girls start to stand out less as they transition from adolescence into young adulthood.